Celebrating Adaptive Delivery: A View from the Frontline in Myanmar - Barnes, Katrina; Lonsdale, Jane (Institute of Development Studies, 2023)
The conversation on adaptive management has grown fast amongst development actors. These conversations often focus on designing, commissioning, and managing large-scale development programmes. Exactly how this impacts the frontline, the implementers, and day-to-day project delivery is still being debated. Yet, perspectives drawn directly from practice are often largely missing within these debates. This paper is written by two development practitioners. Through this paper, we reflect on the difference between adaptive management and adaptive delivery, and how this interacts with risk and aid accountability, particularly in contexts of fragility. Drawing on examples of Oxfam in Myanmar work and our personal insights in relation to delivering programming across humanitarian, peace-building, and development, we suggest that in complex, conflict-affected, and highly political environments adaptive delivery already happens far more regularly than is currently recognised, as a necessity to get activities delivered. However, it happens despite the system, not because of it, and is therefore often hidden and carried out ‘under the radar’ rather than celebrated as a success in difficult environments. This paper was written in 2019, before the military seized control of Myanmar in February 2021. Whilst it draws on examples from pre-2021 Myanmar to illustrate real life cases, it is a contribution to a broader global debate on adaptive management in practice, specifically in fragile contexts. This is not specifically aimed at practitioners working in Myanmar at present, who are now working in a protracted crisis. This paper makes tangible recommendations on steps that donors, international non-governmental organisations, local staff, and partners could take to promote a system of encouraging and celebrating adaptability in programme delivery in fragile contexts.
Accepted: 2023-02-02T14:48:03Z

How adaptive M&E from the peace sector can help demonstrate the value of aid - Kratzer, Sebastian (2023)
Over the last decade, the peace sector has been developing and adapting Monitoring and Evaluation (M&E) systems and tools to fit their contexts and ways of working. This evolution may hold some insights for the aid community in how to go beyond more traditional, backwards-looking M&E to navigate today’s volatile, interest-based world of politics and aid.

Applied political economy analysis for human rights programs and campaigns: A guide for practitioners (second edition) - Pact (Pact, 2023)
This updated guide provides practical guidance to practitioners in the human rights sector and beyond on how to integrate Applied Political Economy Analysis

How to Build Movements with Cyclical Patterns in Mind - Non Profit News | Nonprofit Quarterly - Algoso, Dave; Guerzovich, Florencia; Gattoni, Soledad (Nonprofit Quarterly, 2023)
The world changes too much for anyone who is invested in social change work to imagine that this work is linear and predictable. Opportunities come and go, whether caused by a pandemic or political shifts. This much most social movement leaders and activists intuitively understand. But what can be done with this realization? How might movement groups better prepare for moments of opportunity? We want to explore how we can create the changes we want to see by responding to the changes that are outside our control.

A Guide to Participatory Outcome-Focused Monitoring with Most Significant Change, Outcome Harvesting, and Outcome Mapping - Smith, Richard (CARE, 2023)
Audience This guidance is primarily aimed at development and humanitarian professionals who design or manage monitoring and evaluation processes to support design and implementation of qualitative monitoring using Most Significant Change (MSC), Outcome Harvesting (OH), or Outcome Mapping (OM), which are participatory, outcome-focused qualitative methods. Purpose This guidance is a resource to strengthen qualitative monitoring, specifically addressing commonplace gaps or weakness in the monitoring of complex development and humanitarian projects. Importantly, these gaps include: 1. Lack of evidence about unexpected, as well as expected, changes or outcomes, especially during project implementation. 2. Limited documentation about whether and how a project contributed to change. Such information is vital to learning about what worked and how to build on successes. 3. Limited data to inform the review of theories of change, which limits their function and relevance. Addressing these monitoring gaps has the potential to contribute to more informed and effective adaptive management and learning. This guidance can be used to support the design and implementation of monitoring exercises using MSC, OH, and OM. Specifically, it supports users in choosing among MSC, OH, and OM or blending elements from these approaches. Additionally, it provides practical tips and examples - including expertise gained during the two pilot qualitative monitoring activities conducted in Niger and Bangladesh - as well as other publicly available materials. 1. Relevant CARE guidance and tools include: 1. Qualitative Methods Guidance Note for Monitoring, Evaluation and Learning (MEL) at CARE; 2. Outcome Mapping Manual: Development of a monitoring system for the Right to Food project using Outcome Mapping, CARE Nepal; 3. Tipping Point MEL Methods Brief: Outcome Mapping; 4. The Rolling Profile Tool.